Respostas
respondido por:
2
a)
∆= 2^2 - 4.1.0
∆=4
x1= (-2 + √∆)/2.a
x1= (-2 + 2)/2
x1=0
x2= (-2 - √∆)/2.a
x2= (-2 - 2)/2
x2=-2
b)
∆= (-4)^2 - 4.2.0
∆=16
x1= (4 + √∆)/2.a
x1= (4 + 4)/2
x1=4
x2= (4 - √∆)/2.a
x2= (4 - 4)/2
x2=-0
c)∆=10^2 - 4.5.0
∆=100
x1= (10 + √∆)/2.a
x1= (10 + 10)/2
x1=10
x2= (10 - √∆)/2.a
x2= (10 - 10)/2
x2=0
D)
∆=5^2 - 4.3.0
∆=25
x1= (-5 + √∆)/2.a
x1= (-5 + 5)/2
x1=0
x2= (-5 - √∆)/2.a
x2= (-5 - 5)/2
x2=-5
tmj.
∆= 2^2 - 4.1.0
∆=4
x1= (-2 + √∆)/2.a
x1= (-2 + 2)/2
x1=0
x2= (-2 - √∆)/2.a
x2= (-2 - 2)/2
x2=-2
b)
∆= (-4)^2 - 4.2.0
∆=16
x1= (4 + √∆)/2.a
x1= (4 + 4)/2
x1=4
x2= (4 - √∆)/2.a
x2= (4 - 4)/2
x2=-0
c)∆=10^2 - 4.5.0
∆=100
x1= (10 + √∆)/2.a
x1= (10 + 10)/2
x1=10
x2= (10 - √∆)/2.a
x2= (10 - 10)/2
x2=0
D)
∆=5^2 - 4.3.0
∆=25
x1= (-5 + √∆)/2.a
x1= (-5 + 5)/2
x1=0
x2= (-5 - √∆)/2.a
x2= (-5 - 5)/2
x2=-5
tmj.
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás